High-Functioning Autism, Severe Anxiety, and Bullying in a 26 Year Old. Issue 4 (May 2019) - Fogler, Jason M.; Stein, David; Barbaresi, William J.; Bridgemohan, Carolyn; Steinbauer-Schütz, Andrea; Dirmhirn, Anna; Holzinger, Daniel; Radesky, Jenny; Fellinger, Johannes
Abstract : CASE: Peter is a 26-year-old group home resident in Austria with a history of poor peer relationships, including being bullied, and previous diagnoses of attention-deficit hyperactivity disorder, Asperger syndrome, social anxiety, depression, and developmental coordination disorder. Consultation from our international neurodevelopmental team was requested for severe anxiety and avoidance of social interactions. He reported 4 or more spontaneous anxiety episodes per day. Anxiety triggers included returning to his group home from his vocational rehabilitation program each evening or returning to the group home after weekends at his parents' house. Each Sunday evening, in anticipation of returning to the group home, Peter engaged in tantrums, including screaming and throwing objects and suicidal threats without intent, but not direct aggression toward family members. He phoned his mother several times per day on weekdays. Peter's early history was significant for hyperactivity, impulsivity, aggression, and socially intrusive behavior; he repeated kindergarten and by first grade was characterized as motorically clumsy and "too much in [peers'] personal space." He played alone in kindergarten and had poor social boundaries; when older, he evidenced reduced social perception, and his family reported he did not notice when peers made fun of him. His language developed normally, but he had a "sophisticated style of speaking" and as an adult continued to have trouble understanding gestures, jokes, and social themes in movies. Between ages 7 and 11 years, Peter had been bullied and ostracized by male peers but did well academically, always got along well with adults, and preferred to play with girls. Exclusion by peers persisted through high school, at which time his independent functioning declined and he required his mother's assistance with organizing his materials. At age 15 years, Peter repeated a grade so that he could change classmates, and by the equivalent of his junior year, his grades deteriorated. He had several psychiatric admissions for depression and destructive outbursts (to avoid going to school) and was diagnosed with Asperger disorder. At age 18 years, Peter refused to return to school. He lived at home with his parents, only leaving the house to accompany them on errands, until placed in a group home for people with mental health disorders at age 20 years. At age 26 years, he is sharing a supported-living apartment with 2 young adults with chronic psychiatric disorders. He works in 3 highly structured sheltered workshops for a few hours each and becomes easily overwhelmed in unstructured situations and/or in situations in which he anticipates being reprimanded or letting someone down. Despite a strong interest in marine biology, anxiety prevents him from considering college. How would you proceed with diagnostic testing or intervention to help this young man?